Combined Electronic Nose and Tongue for the Veification of Herbal Products - Mohd Noor, Ahmad, Prof. Dr.; Zhari, Ismail, Prof.; Bahruddin, Saad, Prof.; A.R., Othman, Prof. Madya; A.K.M, Syafiqul Islam, Dr.; Ali Yeon, Md Shakaff, Prof. Dr.; Wahyu, Hidayat; Azlan, Kamil; Abdul Halis (British Inventors Society, 2010)
Prof. Dr. Mohd. Noor Ahmad and his team won gold at British Innovation & Technology Show (BIS), 17th - 20th October 2007 at London.